Ergot threat to sorghum - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Sorghum is an important crop in semi-arid parts of Africa, as well as in other parts of the world. It is a particularly useful crop in that it is more drought-tolerant than many other grain crops. However, the disease ergot or honeydew is becoming a...